O professor e a nova tecnologia da informação - o computador: experiência do PROINFO no piauí - Tarcila Barros Nunes Maranhao (2001)
Utilizing computer in teaching is a complex activity. That led the Brazilian Government (MEC) to elaborate a policy concerning the implementation of a project on the use of New Technologies in Communication and Information (NTCI) in public schools, through the National Curriculum Standards (PCN) and the National Program of Informatics in Education (PROINFO). In individual Brazilian States the project is being implemented by the Center of Education a Technology (NTE). In Teresina, Pi 300 school teachers have already been qualified in the use of computers. Ten of those teachers teach at Liceu Piauiense. In their perception, Brazilian government policy in PROINFO project is extremely valid. They also expressed themselves about the following issues: the qualification of teachers, available resources (hardware and software), teachers performance towards PROINFO and in class, teachers appreciation of the project implementation.